Development Of Mathematics Learning Modules On Relations And Functions - Ramadani, Ayutia; Yahfizham; Siregar, Tanti Jumaisyaroh (Yana Research, 2023)
This study aims to: (1) Know the feasibility of the Mathematics Learning Module used by students in learning mathematics on the subject of Relations and Functions, (2) Know the practicality of the Mathematics Learning Module used by students on learning mathematics on the material of Relations and Functions, (3) Know the effectiveness The Mathematics Learning Module used by students in learning mathematics on the subject of Relations and Functions. The results of the development of this learning module show that the average score obtained shows the criteria of